Chronic inflammatory demyelinating polyneuropathy in a child: Clinical-spinal MR imaging correlation - Likasitwattanakul S. (2014)
Spinal magnetic resonance (MR) imaging of a 3-year-old girl with chronic inflammatory demyelinating polyneuropathy (CIDP) showed thickened and marked enhancement of the lumbosacral nerve roots. These abnormalities resolved after steroid treatment. MR imaging of the cauda equina may be helpful in the diagnosis of CIDP.